2021
DOI: 10.1016/j.scriptamat.2021.113820
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale oxidation behavior of carbon fibers revealed with in situ gas cell STEM

Abstract: Thermal protection systems (TPS) are used to protect spacecraft payloads during the extreme conditions of atmospheric entry. The backbone of the composite TPS material used in the NASA Stardust Sample Return Capsule and the Mars 2020 mission is carbon fiber, which oxidizes at these temperatures and atmospheric conditions. This study presents the direct observation of carbon oxidation using in situ Scanning Transmission Electron Microscopy (STEM). A thin section of a commercially-available carbon fiber material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…At 1223 K, we approximate the etch rate of a disordered carbon fiber structure to be 1.75 nm/s from their results (by assuming the thickness of their carbon fiber strip to be 1.5 μm). We expect the value of this rate to be higher than the in-depth etch rate of pure graphite due to the higher number of active sites available for oxygen adsorption in carbon fiber than in graphite . In extrapolating our curve to slightly lower temperatures, around 1223 K, our prediction for the in-depth etch rate at this temperature would be approximately 1 nm/s.…”
Section: Results and Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…At 1223 K, we approximate the etch rate of a disordered carbon fiber structure to be 1.75 nm/s from their results (by assuming the thickness of their carbon fiber strip to be 1.5 μm). We expect the value of this rate to be higher than the in-depth etch rate of pure graphite due to the higher number of active sites available for oxygen adsorption in carbon fiber than in graphite . In extrapolating our curve to slightly lower temperatures, around 1223 K, our prediction for the in-depth etch rate at this temperature would be approximately 1 nm/s.…”
Section: Results and Discussionmentioning
confidence: 74%
“…There may also be other reactions occurring at higher temperatures that are not included in our KMC model. The result of their experiments at higher temperatures (2478 K) at 1 atm (101,325 Pa) is on the same order of magnitude, 10 4 nm/s, as the in-depth etch rate calculated in our work at high temperatures (2500 K) at 0.099 atm (10,000 Pa) when the curve in Figure is extrapolated to 2500 K. Cochell et al conducted experiments on the oxidation of a thin strip of carbon fiber at a fixed pressure of 10,132 Pa and varying temperature . At 1223 K, we approximate the etch rate of a disordered carbon fiber structure to be 1.75 nm/s from their results (by assuming the thickness of their carbon fiber strip to be 1.5 μm).…”
Section: Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This study revealed the nonuniform oxidative mechanism of the material due to its dependence on microstructure. 58 Reductive mechanisms can be similarly investigated using reducing gases such as H 2 in the gas cell. The effect of silica on iron oxide reduction was reported under 700−950 mbar H 2 atmosphere at 750 °C, where comparative studies were performed on silica-promoted and unpromoted iron oxide samples.…”
Section: ■ Applications and Examplesmentioning
confidence: 99%